2012
DOI: 10.1055/s-0032-1312848
|View full text |Cite
|
Sign up to set email alerts
|

Klinischer Stellenwert der Durchleuchtung der Magen-Darm-Passage (MDP) an einem Universitätsklinikum

Abstract: Considering the wide availability of modern sectional imaging methods that are usually necessary for taking significant therapeutic steps, the indication for FTE examinations of the gastrointestinal tract should be very restrictive. The relatively high radiation exposure supports this suggestion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Even if in total 3.5 % (n = 75) more anatomical structures or foreign material was able to be detected on images acquired in a lying position, this information was not diagnostically relevant in a single case so that routine acquisition of images in a lying position as a supplement to images in a standing position or in a leftlateral position is no longer to be viewed as indicated in the majority of cases. A further publication from the same working group retrospectively examined the value of conventional fluoroscopy of the gastrointestinal passage in 300 patients of a university hospital [131]. In this study the authors found that a further diagnostic imaging method such as endoscopy, CT, or ultrasound was initiated in over 87 % of patients who underwent gastrointestinal passage prior to a change in diagnosis or treatment.…”
Section: Venous Occlusionmentioning
confidence: 99%
“…Even if in total 3.5 % (n = 75) more anatomical structures or foreign material was able to be detected on images acquired in a lying position, this information was not diagnostically relevant in a single case so that routine acquisition of images in a lying position as a supplement to images in a standing position or in a leftlateral position is no longer to be viewed as indicated in the majority of cases. A further publication from the same working group retrospectively examined the value of conventional fluoroscopy of the gastrointestinal passage in 300 patients of a university hospital [131]. In this study the authors found that a further diagnostic imaging method such as endoscopy, CT, or ultrasound was initiated in over 87 % of patients who underwent gastrointestinal passage prior to a change in diagnosis or treatment.…”
Section: Venous Occlusionmentioning
confidence: 99%